Optimization of Pasteurization Conditions for Pineapple Juice Quality Preservations - Ahmad Nizam, Nur Mujahidah; Abdullah, Norazlin (Enhanced Knowledge in Sciences and Technology, 2023)
The purpose of this study is to investigate the effect of pasteurization on pineapple juice using N36 variety by optimization of pasteurization conditions which are temperature and time. The optimization was done using Design Expert 13 with central composite design (CCD) method. The pasteurization was done accordingly within the range of 75 ̊ C until 95 ̊ C at 10 seconds until 1800 seconds. Total soluble solids, ascorbic acid content and bromelain activity was determined as the response from the optimization of pasteurization. Fresh pineapple juice which is unpasteurized sample was assessed for its physicochemical properties, nutritive qualities, and microbiological count to compare these attributes with pasteurized samples. This study found that optimal pasteurization settings of pineapple juice are at temperature 80.5 C for 1133 seconds / 18 minutes, with desirability near to 1 (0.961). The response of total soluble solids, ascorbic acid content and bromelain activity are all maximize and yielded values of 9.743847 Brix, 0.06241 mg/L, and 0.026157 CDU/mL, respectively.